Surface properties of mycoparasitic Pythium species and their interaction with model materials - Majtan, Katarina; Klimentić, Maja; Martinik, Jan; Kulisova, Marketa; Jarosova, Irena; Potocar, Tomas; Branyik, Tomas (Heliyon, 2024)
Pythium oligandrum, a soil-born oomycete, is an effective biological control agent exhibiting antagonistic and parasitic activity against pathogenic fungi. This study is the first attempt to characterize its surface properties and to apply models of physicochemical interactions (thermodynamic, DLVO and XDLVO) to quantify its adhesion properties to a model material, represented by magnetic beads (MB). The predictions of interaction models were based on experimental data (contact angles, zeta potentials, size). Adhesion intensities (AI) were determined experimentally taking advantage of MB with different surface properties. The role of weak physicochemical interactions was estimated by comparing experimental AI with model predictions. The results revealed that the surface properties of the three Pythium spp. studied were very similar and fell within the range for hydrophilic microorganisms (ΔGTOT > 0) with a predominantly negative surface charge. The most reliable description of AI was obtained using the DLVO model, including Lifshitz-van der Waals and electrostatic interactions. The highest AI between Pythium spp. and all three MB was observed at pH 3, which was supported by the DLVO prediction. The greater agreement between the sphere-sphere geometric version of the DLVO model and experiment suggests that the surface protrusions of the oospores increase the efficiency of adhesion. The surface properties of the pathogenic fungi, characterized in this work, fell within the range defined by MB and therefore it can be expected that their physicochemical interactions with Pythium spp. will also be favourable.
Keywords: Pythium species; Model materials; Adhesion; (X)DLVO model; Thermodynamic model; Surface interaction